1974
DOI: 10.1063/1.1682227
|View full text |Cite
|
Sign up to set email alerts
|

Crossed molecular beam study of reactive scattering: O + CS2 →SO + CS

Abstract: The angular distribution and velocity of SO reactively scattered from crossed molecular beams of oxygen atoms and CS2 have been measured. In c.m. coordinates, the SO is strongly forward scattered with an in plane angular distribution represented by exp(−θ/50°), indicating a direct reaction mechanism. The mean recoil velocity of SO is independent of the c.m. angle, showing that the average fraction of reaction exoergicity appearing as translational energy of product separation is <10%. Combined with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

1975
1975
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 15 publications
2
6
0
1
Order By: Relevance
“…Having measured the angular distribution and velocity of SO reactively scattered from crossed molecular beams of oxygen atoms and CS 2 , Geddes et al observed the SO is strongly forward scattered, indicating a stripping reaction. 17 They showed that most of the energy is released into rotational degrees of freedom of products and the reaction proceeds via highly bent intermediate configurations. No OCS signal was detectable in their experiments consistent with the much smaller rate constant of the reaction channel R2.…”
Section: R3mentioning
confidence: 99%
See 1 more Smart Citation
“…Having measured the angular distribution and velocity of SO reactively scattered from crossed molecular beams of oxygen atoms and CS 2 , Geddes et al observed the SO is strongly forward scattered, indicating a stripping reaction. 17 They showed that most of the energy is released into rotational degrees of freedom of products and the reaction proceeds via highly bent intermediate configurations. No OCS signal was detectable in their experiments consistent with the much smaller rate constant of the reaction channel R2.…”
Section: R3mentioning
confidence: 99%
“…The reaction of oxygen atom O( 3 P) with carbon disulfide, CS 2 , has received considerable scrutiny because of its importance in CS 2 −O 2 chemical lasers. Three possible exothermic channels have been identified for this reaction: normalO false( 3 normalP false) + CS 2 CS + SO false( 3 false) normalR1 OCS + normalS false( normalP 3 false) normalR2 CO + normalS 2 false( 3 normalg false) normalR3 It is revealed by several experimental studies that the major primary step is the reaction channel R1, which provides CS for producing chemical CO lasers through the important secondary reaction normalO false( 3 normalP false) + CS CO normal⧧ + normalS...…”
Section: Introductionmentioning
confidence: 99%
“…Recently CO product vibrational-rotational state distributions have been reported3 using UV photolysis IR probe measurements on the O + OCS reaction, which show high rotational excitation of the reaction products. Further cross beam reactive scattering experiments have therefore been undertaken using a high temperature radio frequency (RF) discharge source4 to gain an enhanced initial translational energy E ~85 kj mol-1 in studies of the SO reactive scattering from both of the reactions O + OCS -* SO + CO (1) O + CS2 -SO + cs (2) under closely comparable conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2. Typical transient absorption signals for OCS and CO. Spectral lines probed are OCS (00°0) R(5) and CO(u=0) P(10). Each trace represents the average of four laser shots and is scaled to the YAG laser…”
mentioning
confidence: 99%